2018
DOI: 10.1136/bmjqs-2018-007894
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term effects of a team-based quality improvement training programme

Abstract: A team-based QI training programme resulted in a high degree of participants' involvement in QI activities beyond completion of the programme. A majority of team projects showed improvement in project measures, often occurring after completion of the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…O’Leary and colleagues in their article nicely demonstrate the causal link between QI education and the acquisition of QI knowledge and skills,8 and this link has been demonstrated previously by others 4 7. The next logical link is to determine if these newly acquired knowledge, skills and attitudes result in behavioural change for the learner.…”
Section: Linking Qi Education To Long-term Improvements In Outcomes Tsupporting
confidence: 53%
See 2 more Smart Citations
“…O’Leary and colleagues in their article nicely demonstrate the causal link between QI education and the acquisition of QI knowledge and skills,8 and this link has been demonstrated previously by others 4 7. The next logical link is to determine if these newly acquired knowledge, skills and attitudes result in behavioural change for the learner.…”
Section: Linking Qi Education To Long-term Improvements In Outcomes Tsupporting
confidence: 53%
“…Some simple ones are easy to imagine. Do learners take on a new improvement project after completing the curriculum?16 In this instance, we commend O’Leary and colleagues, as their study is one of a minority of studies that actually reports on future involvement in QI work (48% of their graduates reported taking on a new QI project within 18 months of completing the programme) 8. However, other less tangible behaviours are difficult to measure, yet critically important to capture.…”
Section: Linking Qi Education To Long-term Improvements In Outcomes Tmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The team-based approach to quality improvement has been shown to be beneficial not only in the initial phases of improvement but with sustainability of results. 13 Having voices from all areas of the clinical system present through the improvement process gives a wider scope of the issues at hand as well as potential solutions. 14 Before this study, our team collected data on low acuity pediatric emergency department visits and found that tailoring our interventions toward patient level interventions using a team-based approach was successful in decreasing these types of visits.…”
Section: Introductionmentioning
confidence: 99%
“…Current assessment approaches have largely focused on ‘hard’ skills. For example, the QI Knowledge Application Tool,18 one of the most widely referenced assessment tools in QI,19 20 asks learners to create an aim statement, define a measure and propose a change for a given QI problem. However, evaluating a broader set of QIPS abilities will likely require other assessment approaches, such as reflective practice, portfolios and multisource feedback, as alternative ways of assessing the range of skills.…”
mentioning
confidence: 99%